Phylogenetic analysis reveals high local endemism and clear biogeographic breaks in southern African stoneflies (Notonemouridae, Plecoptera) - Stevens, Duncan M.; Bishop, Jacqueline; Picker, Mike D. (Zootaxa, 2018)
The low vagility of the southern African Notonemouridae (stoneflies, Plecoptera), and their restriction to temperate montane refugia, make them a useful model for examining the evolution and biogeography of the rich palaeogenic fauna of the region. Here we use maximum parsimony tree reconstruction based on morphological characters and a partial COI mtDNA sequence to explore the evolutionary history and biogeography of the family in southern Africa. Morphological and molecular parsimony cladograms were largely in agreement, and supported monophyly of all six genera in the region. Previously undocumented morphological features in Plecoptera are identified: the first record of paraproct glands, and the presence of paired spermathecae in Aphanicercopsis Barnard females (all other Plecoptera have a single or a divided spermatheca). Some phylogenetically useful characters were the degree of fusion of the ventral abdominal nerve cord ganglia, male paraproct glands (presence and shape), and accessory glands of the male seminal vesicle. Two main biogeographic zones were defined: Eastern Highlands and the Cape Fold Mountains, with an additional outlying zone, the Namaqualand Highlands. Almost 41% of species were endemic to a single mountain range group. The most species-rich region was the intersection of the Southern and Western Cape Fold Mountains. It is hypothesized that, after the separation of Gondwanaland, the common ancestor of the region’s six genera dispersed from a Cape Fold Mountain origin to the Amatola and Drakensberg montane areas of the southern tip of the African continent. The high number of species within the Cape Fold Mountains compared to other mountain ranges in the region is likely a reflection of the topographic complexity of this mountain system and its influence on vicariant events.